Quantifying the Impact of Economic Sanctions on International Trade in the Energy and Mining Sectors - Mario Larch; Serge Shikher; Constantinos Syropoulos; Yoto V. Yotov (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Capitalizing on the latest developments in the gravity literature, we utilize two new datasets on sanctions and trade to study the impact of economic sanctions on international trade in the mining sector, which includes oil and natural gas. We demonstrate that the gravity equation is well suited to model bilateral trade in mining and find that sanctions have been effective in impeding mining trade. Our analysis reveals that complete trade sanctions have reduced bilateral mining trade by about 44 percent on average. We also document the presence of significant heterogeneity in the effects of sanctions on mining trade across mining industries and across sanction episodes/cases, depending on the sanctioning and sanctioned countries, the type of sanctions used, and the direction of trade flows. We take a close look at the impact of recent sanctions on Iran and Russia.
Keywords: F10; F13; F14; F50; F51; H50; N40; 330; structural gravity; sanctions; mining; oil; trade effects